Nonverbal learning disability: a tutorial for speech-language pathologists. - Volden J (American Journal of Speech-Language Pathology, 2004)
Nonverbal learning disability (NLD) is a diagnostic category that is unfamiliar to most speech-language pathologists. This brief tutorial describes NLD's characteristics, a theoretical model proposed to explain its source, and areas of overlap between NLD and similar diagnostic categories. The communicative profile, made up of difficulties in pragmatic and semantic language in the presence of relatively preserved syntactic skill, is also discussed. Empirical evidence relevant to NLD is also evaluated. Many questions remain unresolved, but until systematic research provides definitive answers, speech-language pathologists are encouraged to rely on careful description of the individual child's communicative strengths and weaknesses to identify appropriate targets and to focus intervention on improving the child's ability to communicate effectively in everyday contexts.